Barriers of Applying Building Information Modelling (BIM) According to BIM ISO - Kong, Sio Kah; Ho, Ming Qin (INTI International University, 2022)
BIM is not new but it is still not widely applied in Malaysian construction industry. Many have claimed to have adopted BIM but failed to have applied BIM in accordance to BIM ISO standards. The issues of cost overrun and time overrun persisted in the BIM construction projects. BIM proved to have various tools that will definitely mitigate the issues but not many are familiar with BIM ISO 19650 to unleash the full potential of BIM. BIM ISO is a standard to manage the information for a project. This research is aimed to evaluate the barriers of apply BIM to the standards of BIM ISO 19650 during design phase in the construction industry in Johor, Malaysia. Online questionnaire is sent through email to the building designers – architects and engineers. After the primary data is collected, the findings are displayed with relative importance index (RII). This research has discovered the low practice level of BIM in Johor is mainly due to the barrier of lack of detail and guidance of national standard.